Compatibility of a novel filter paper-based bio-safe sputum transport kit with line probe assay for diagnosing drug-resistant tuberculosis: a single-site evaluation study. Issue 3 (2nd August 2021) - Anthwal, Divya; Gupta, Rakesh Kumar; Singhal, Ritu; Bhalla, Manpreet; Verma, Ajoy Kumar; Khayyam, Khalid Umar; Myneedu, Vithal Prasad; Sarin, Rohit; Gupta, Ashawant; Gupta, Nalini Kant; Singh, Manjula; Sivaswami Tyagi, Jaya; et al.
Background: Near-patient access to appropriate tests is a major obstacle for the efficient diagnosis of tuberculosis (TB) and associated drug resistance. Methods: We recently developed the "TB Concentration & Transport" kit for bio-safe, ambient-temperature transportation of dried sputum on Trans -Filter, and the "TB DNA Extraction" kit for DNA extraction from Trans -Filter for determining drug resistance by DNA sequencing. In the present study, we evaluated the compatibility of Kit-extracted DNA with Hain's line probe assays (LPAs), which are endorsed by National TB programmes for the detection of drug resistance in sputum collected from presumptive multidrug-resistant TB patients ( n =207). Results: Trans -Filter-extracted DNA was seamlessly integrated with the LPA protocol (Kit-LPA). The sensitivity of Kit-LPA for determining drug resistance was 83.3% for rifampicin (95% CI 52–98%), 77.7% for isoniazid (95% CI 52–94%), 85.7% for fluoroquinolones (95% CI 42–100%) and 66.6% for aminoglycosides (95% CI 9–99%), with a specificity range of 93.7% (95% CI 87–97) to 99.1% (95% CI 95–100) using phenotypic drug susceptibility testing (DST) as a reference standard. A high degree of concordance was noted between results obtained from Kit-LPA and LPA (99% to 100% (κ value: 0.83–1.0)). Conclusions: This study demonstrates successful integration of our developed kits with LPA. The adoption of these kits across Designated Microscopy Centres in India can potentially overcome the existing challenge of transporting infectious sputum at controlled temperature to centralised testing laboratories and can provide rapid near-patient cost-effective "Universal DST" services to TB subjects residing in remote areas. The adoption of bio-safe "TB Concentration & Transport" kit by Microscopy Centres can potentially overcome the challenge of transporting infectious sputum to central laboratories and provide universal DST services to TB subjects residing in remote areas. https://bit.ly/2QrQ5qL